Following Sextus: Demonstrative Argument in Gorgias’ Peri tou mē ontos - Giombini, Stefania (Peitho. Examina Antiqua, 2018)
The two extant versions of Gorgias’ Peri tou mē ontos (PTMO) have been preserved by an anonymous author (MXG) and by Sextus Empiricus (S.E.). Both versions have been differently interpreted by scholars who examine either the doctrine or the rhetorical-communicational dimension (the first option being dominant). When comparing the PTMO with the rest of Gorgias’ works, the present paper aims to demonstrate that S.E. offers a more precise account of Gorgias’ modus argumentandi. Thus, S.E. shows the following, typical features of Gorgias’ demonstrative reasoning: 1) application of demonstrandum and quod erat demonstrandum, 2) continuous employment of reductio ad absurdum and 3) a refined formulation of the principle of non-contradiction (similar to the one in Pal. 25). The MXG, on the other hand, is accurate in the discussion of particular arguments (e.g. the third kephalaion), but presents an interpreter who is more interested in questioning Gorgias rather than doing justice to his thought. Hence, this article concludes that it was S.E., who had the text or at least a relatively accurate summary of the PTMO.